1991
DOI: 10.1116/1.585578
|View full text |Cite
|
Sign up to set email alerts
|

Gate oxide damage from polysilicon etching

Abstract: Damage to thin gate oxides from etching of polysilicon gates was studied using gate oxide breakdown histograms and time-dependent dielectric breakdown measurements. The effect of various polysilicon etch parameters was investigated in a radio frequency (rf) triode etcher. Increasing rf power caused a substantial increase in damage. Reducing bias at constant power also resulted in an increase in damage, indicating that ion energy is not the only cause of damage. Area, isolation edge, and source/drain edge contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…By comparison, the number of test structures on a wafer ( ) is on the order of 20 000. Consequently, we can neglect the capacitance ratio compared to in the denominator of (8), so it becomes (9) The potential of the silicon substrate is thus the average potential on the gates of the test structures. Since the test structures are located uniformly across the surface of the wafer, we can approximate the potential of the silicon substrate as the average potential across the surface of the wafer.…”
Section: Pre-breakdown Equivalent-circuit Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, the number of test structures on a wafer ( ) is on the order of 20 000. Consequently, we can neglect the capacitance ratio compared to in the denominator of (8), so it becomes (9) The potential of the silicon substrate is thus the average potential on the gates of the test structures. Since the test structures are located uniformly across the surface of the wafer, we can approximate the potential of the silicon substrate as the average potential across the surface of the wafer.…”
Section: Pre-breakdown Equivalent-circuit Modelmentioning
confidence: 99%
“…This damage is the result of exposure to the various particle and energy fluxes present in the plasma environment and for gate oxides can be caused by wafer surface charging, [7]- [9]. The damage generated by this charging is the result of Fowler-Nordheim (F-N) current stressing of thin oxides under floating gates, [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have shown that the thin oxide under the gate electrode can be damaged during gate etching. [1][2][3][4] This damage probably occurs as a result of charge from the plasma entering the exposed edges of the resist-masked gate electrode. 5,6 Earlier work found that damage occurs primarily at or near the polysilicon endpoint, with subsequent overetching having little effect on it.…”
Section: Introductionmentioning
confidence: 99%
“…As feature sizes drop below 100 nm, UV radiation and feature charging are predicted to be the primary cause of device damage. 98 In addition, particle generation, which is extensive in reactive plasma atmospheres, is a concern, and methods to both minimize particle generation and remove particles after etch and deposition are needed. [99][100][101][102] Small feature sizes (Ͻ500 nm) and low pressure (Ͻ5 mTorr) reactors have generated their own set of pattern distortions and uniformity problems including aspect ratio dependent etching and microloading.…”
Section: Plasma Processingmentioning
confidence: 99%